Guidance Note for Fund Staff on the Treatment and Use of SDR Allocations. (Policy Papers; Policy Paper ;, 2009)
Against the backdrop of the global financial crisis, the IMF has decided to implement a USD 250 billion general allocation of special drawing rights (SDRs). In addition, the Fourth Amendment of the Fund's Articles of Agreement has recently become effective, and will make available to SDR Department participants a special allocation of up to an additional SDR 21.5 billion (USD 33 billion). Nearly USD 115 billion of these combined allocations will go to emerging market and developing countries, including about USD 20 billion to low-income countries (LICs), thereby providing an important boost to the reserves of countries with the greatest needs.